Justice in the Digital Age: Evaluating the Impact and Integrity of Virtual Hearings in Makati City - Argel Anthony V. Chua (Future Science / FSH-PH Publications, 2026)
During the height of COVID-19 pandemic, courts around the globe rely mostly on videoconferencing to sustain judicial processes and that their operations remain unhampered. In the Philippines, particularly in Makati City, the adoption of videoconferencing became part of the judicial system even after the pandemic. However, this opened questions about its integrity and effectiveness. With the use of qualitative phenomenological research design guided by Colizzi’s method, this study focuses on the evaluation and impact of videoconferencing specifically on safety and security measures, ability to present cases, procedural integrity, and technical challenges encountered by the selected participants. A total of ten (10) participants which include litigants, lawyers, prosecutors, court personnel, and law enforcement officers who are directly involved or had experience attending virtual hearing have been interviewed. The study collected data through in-depth interviews and focus group discussions. With the direction of the Philippine government towards digitalization, local studies remain limited to quantitative evaluation of user satisfaction in the use of videoconferencing. Additionally, the findings from previous studies highlight the urgent need for robust digital infrastructure, enhanced training, and policy refinement to ensure fairness and protect legal rights in virtual courtrooms. This study, on the other hand, includes findings on the workarounds adapted by the stakeholders to balance and bridge the transition from traditional and virtual courtroom setup such as the use hybridized practices during presentation and marking of evidence, where physical records complement virtual hearings.